Liveworksheet-Based E-LAPD to Enhance Students’ Critical Thinking in Chemical Equilibrium - Nabila Aulia; Sukarmin (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study focuses on developing interactive multimedia in the form of a Liveworksheet-based Electronic Student Activity Sheet (E-LAPD) designed to enhance students' critical thinking ability in chemical equilibrium. The research employs Thiagarajan's 4D model (Define, Design, Develop, and Disseminate), limited to the Develop stage. The study evaluates the E-LAPD's validity, practicality, and effectiveness. Validity was assessed by three experts using a Likert scale through content and construct validation, with results indicating that the E-LAPD met valid criteria across all assessed aspects. Practicality was determined through quantitative descriptive analysis of student response questionnaires and activity observation sheets, demonstrating a very practical rating supported by consistently high relevant student activity percentages across three sessions. Effectiveness was measured using N-Gain scores and a paired-sample t-test comparing pretest and posttest critical thinking scores, which revealed statistically significant improvement with N-Gain scores ranging across moderate-to-high categories. These outcomes collectively affirm that the Liveworksheet-based E-LAPD is a valid, practical, and effective learning tool. The guided inquiry approach integrated into the E-LAPD promotes active student engagement and fosters the development of critical thinking across all indicators, underscoring its strong potential as an innovative instructional medium for advancing higher-order thinking skills in chemistry education.